Implementasi Model Layanan Bimbingan dan Konseling untuk Meningkatkan Kesehatan Mental Siswa: Analisis Efektivitas Dukungan Sistem Berbasis ͑Model Edwards III - Sri Mustika; Rosemila Amalia; Dinny Mardiana; Suharyanto H. Soro (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Adolescent mental health is currently in an alarming condition; national data indicate that approximately one in three Indonesian adolescents (34.9%) experience mental health problems, with significant increases in anxiety and depression cases in the post-pandemic period. This study aims to analyze the implementation of the Guidance and Counseling (GC) model at SMPN 43 Bandung using Edwards III Policy Implementation Model as the analytical framework. This research employed a qualitative case study approach with data collected through in-depth interviews and observations. The findings reveal that communication through In-House Training (IHT) ensures shared understanding and alignment between school leaders and implementers, while adequate budgeting and well-facilitated counseling rooms serve as key determinants of success, distinguishing this school from previous studies. The autonomous bureaucratic structure and formal collaboration through the TPPK Team, ESQ Training, Character Building initiatives, and the Homeroom Teacher Program establish an efficient referral system. Furthermore, the empathetic attitude of GC practitioners successfully eliminates the stigma commonly attached to counseling services, leading to a significant increase in students’ help-seeking behavior. However, the study also identifies gaps in the technical competence of GC teachers, particularly the need for enhanced mastery of advanced clinical counseling techniques. The study concludes that the implementation of GC services at SMPN 43 Bandung is highly effective due to the integration of strong managerial commitment and robust systemic support. This success demonstrates that eliminating instrumental barriers directly contributes to creating a healthy and stigma-free school climate. The model has strong potential to serve as a best practice reference for other educational institutions in managing adolescent mental health.